2020
DOI: 10.1088/2515-7655/ab78ef
|View full text |Cite
|
Sign up to set email alerts
|

Formation of stable 2D methylammonium antimony iodide phase for lead-free perovskite-like solar cells*

Abstract: The presence of lead in novel hybrid perovskite-based solar cells remains a significant issue regarding commercial applications. Therefore, antimony-based perovskite-like A 3 M 2 X 9 structures are promising new candidates for low toxicity photovoltaic applications. So far, MA 3 Sb 2 I 9 was reported to only crystallize in the 'zero-dimensional' (0D) dimer structure with wide indirect bandgap properties. However, the formation of the 2D layered polymorph is more suitable for solar cell applications due to its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Although the i‐SLMEs of the 0D compound are low, recent work has shown that the 2D phase can be stabilized, leading to a near‐direct bandgap (which allows higher absorption coefficients) and a lower bandgap value of 2.1 eV (which is closer to the optimum for IPV). [ 84 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the i‐SLMEs of the 0D compound are low, recent work has shown that the 2D phase can be stabilized, leading to a near‐direct bandgap (which allows higher absorption coefficients) and a lower bandgap value of 2.1 eV (which is closer to the optimum for IPV). [ 84 ]…”
Section: Resultsmentioning
confidence: 99%
“…Although the i-SLMEs of the 0D compound are low, recent work has shown that the 2D phase can be stabilized, leading to a near-direct bandgap (which allows higher absorption coefficients) and a lower bandgap value of 2.1 eV (which is closer to the optimum for IPV). [84] InI is another material with high i-SLMEs of 53%. However, InI devices have demonstrated relatively poor 1-sun photovoltaic efficiencies of ≈0.4%.…”
Section: Future Ipv Potential Of Lead-free Perovskite-inspired Materialsmentioning
confidence: 99%
“…[ 36 ] We note that although the bandgap is significantly underestimated, we can assume that the DFT‐PBE method provides accurate predictions about the electronic nature of the calculated structure. [ 60,61 ] Hence, a direct bandgap with an energy of 2.8 eV was obtained (Figure S11, Supporting Information), increasing the energy by 0.6 eV compared to the 3D Cs 2 AgBiBr 6 . [ 17 ]…”
Section: Resultsmentioning
confidence: 99%
“…5 In particular, the 2D polymorph is more desirable for photovoltaics owing to the higher mobility and defect tolerance than the 0D counterpart. [6][7][8][9][10] Strictly speaking, Cs 3 Sb 2 I 9 is not a perovskite but a perovskite derivative or perovskite-inspired material. 11,12 In this paper, however, the term perovskite is in some occasion used broadly to cover also the perovskite derivatives.…”
Section: Introductionmentioning
confidence: 99%